Einführung: Die Erzeugung religiös-weltanschaulicher Vielfalt (Pedagogical Horizons, 2020)
Intoduction to the special issue: 'Construction of religious and worldview pluralism' that represents the actual research on the topic and brings forward a multi-level modell of religious and worldview pluralism that will also help to systematise the contributions of this special issue.
Keywords: religious pluralism; worldview; worldview studies; difference